State of charge estimation of lithium-ion batteries using adaptive neuro fuzzy inference system - Imane Chaoufi; Othmane Abdelkhalek; Brahim Gasbaoui (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
A battery’s state of charge (SOC) is used to assess its residual capacity. It is a very important parameter for the control of the electric vehicle (EV). The objective of this paper is to estimate the SOC of a lithium-ion battery (LIB) using an adaptive neuro-fuzzy inference system (ANFIS) and artificial neural network (ANN) because SOC of a battery must be estimated from measurable battery parameters such as current, voltage or temperature. Two intelligent SOC estimation methods are compared according to their suitability and accuracy. ANN estimation is more precise and perfectly represents the experimental data.